ORGANIZING PHYSICAL EDUCATIONAL EVENTS WITH PRESCHOOL CHILDREN - Nuriddinova, Muyassar (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The information on organizing physical educational events with preschoolers are given by this article.